Can a targeted educational approach improve situational awareness in paramedicine during 911 emergency calls?. (July 2022) - Hunter, Justin; Porter, Michael; Cody, Patrick; Williams, Brett
Highlights: The situational awareness of paramedics was measured in real-time during 911 calls in the U.S. A novel quick reference tool has been created to improve situational awareness in the out-of-hospital setting. The situational awareness of paramedics may improve, during 911 calls, with a targeted educational approach utilizing crew resource management and the use of a novel quick reference tool. Situational awareness research in paramedicine is lacking. Abstract: Background: Paramedics must be situationally aware in order to avoid human error and protect themselves, their partner, their patient, and the public. Previous research has suggested that paramedics lack situational awareness (SA), possibly due to a lack of an organized approach, distraction, and a poor understanding of SA. There is no educational approach provided to paramedics that is known to improve their levels of SA. If such an approach were provided, it could possibly reduce human error and lead to improved outcomes. Objective: The aim of this study is to determine whether providing paramedics with a targeted educational approach, including aspects from crew resource management (CRM) such as sterile cockpit and Endsley's model for SA, can improve overall SA during emergency calls. Methods: A prospective, quasi-experimental before-and-after study was used, in which out-of hospital paramedics were observed during 911 emergency calls. Baseline SA was measured using the situational awareness global assessment technique (SAGAT). Paramedics were then given a targeted educational lesson focusing on elements of SA and CRM as well as a novel quick reference tool to utilize during 911 calls. Post intervention SA was then measured again, and before-and-after results were compared for difference of mean scores. Results: The overall baseline SA was 62% increasing to 86% following the educational intervention. The Wilcoxon Ranked Sum was used to assess for statistically significant differences between mean SA performance in the same group of paramedics before and after the intervention. The increase in SA was found to be statistically significant where p = 0.011. Conclusions: A targeted educational approach focusing on CRM and a novel quick reference tool may increase SA levels of paramedics during 911 emergency calls. Further studies are needed with bigger cohorts. Paramedicine educational institutions and out-of-hospital agencies should consider implementing this targeted approach with their students and currently practicing providers.